Beyond the log frame: a new tool for examining health and peacebuilding initiatives - and Grove, Natalie J.; Zwi, Anthony B. (Development in Practice, 2008)
How do we move from identifying ethical principles to enhancing development practice? How can donors and NGOs move beyond the reporting of technical outputs to explore less tangible aspects of their health projects: contributions to rebuilding trust, promoting social cohesion, and enhancing good governance at community level? This article considers these questions in relation to health and peace-building activities in conflicted settings. It describes difficulties facing practitioners and donors seeking to undertake health and peace work, in particular focusing on the lack of appropriate tools for screening, monitoring, and evaluating projects. It critiques the logical framework, a tool commonly used in project planning, monitoring, and evaluation, and considers it alongside a new tool, the Health and Peace Building Filter, which has been designed to reflect on health programming in fragile or conflicted settings. The authors argue that such tools can help to move us beyond focusing on inputs and outputs to examining processes, relationships, and the indirect consequences of aid programmes.